The effects of adapted physical education sessions on the empathy of female students with overweight - Slimi, Oumayma; Marsigliante, Santo; Ciardo, Vito; Bahloul, Mourad; Selmi, Okba; Jebabli, Nidhal; Muscella, Antonella (Frontiers in Psychology, 2023)
The global prevalence of childhood and adolescent overweight and obesity increases rapidly. Physical activity plays a major role in the prevention of obesity. The present study aimed to analyze the effect of adapted basketball sessions according to the empathic capacity of adolescent girls with overweight. Forty-two girls with overweight (age: 16.09 ± 0.85; years; height: 1.64 ± 0.67 m: weight: 73.02 ± 0.61 kg; BMI: 27.15 ± 1.37) volunteered to participate in the study and were randomly assigned to the experimental group (EG, n = 21) and control group (CG, n = 21). EG was submitted to a basketball intervention adapted to students with obesity while the CG performed classic basketball exercises for 7 weeks. Each week girls had 2 basketball teaching-learning sessions, lasting 50 min. The participants’ empathy was assessed before and after the intervention using the Favre CEC. The results showed that adaptation intervention was associated with a significant emotional contagion decrease (Δ% = 0.466) and splitting with emotions (Δ% = 0.375), and with an empathy increase (Δ% = 1.387), in EG compared to CG. No significant difference was assessed in the empathy CG, before and after the intervention. This study demonstrated that adapted physical education classes could be an effective strategy to improve empathetic skills and inclusion of overweight girls as well as a means to prevent obesity.